Penggunaan kantong nilai untuk meningkatkan kemampuan berhitung penjumlahan dan pengurangan pada peserta didik kelas I sekolah dasar - Budiarti, Yayuk (Universitas Sebelas Maret, 2021)
The purpose of this study was to improve the addition and subtraction arithmetic ability of the class IB students of SD Negeri Karanganyar 2 in the 2020/2021 school year. The form of this research is Classroom Action Research with 2 cycles consisting of 1 learning per cycle. The learning steps include planning, implementing actions, observing, and reflecting. The research subjects were IB class students consisting of 17 students, 5 male students and 12 female students. Data collection techniques used were observation, interviews, tests, and documents. The results of the research analysis in the first cycle showed that the average score of students who were above the KKM reached 72 with 59% classical completeness or as many as 10 students. Cycle II increased to 81 the average score with classical completeness 88% or as many as 15 students. The conclusion of this study is that the use of value bags can increase the ability to count addition and subtraction in class IB semester 1 students of SD Negeri Karanganyar 2 in the 2020/2021 academic year.